Учет интервальной неопределенности при принятии решений - Брынза, Н. А. (ХНУРЭ, 2008)
The problem of decision making under the conditions of uncertainty occupies at present special position in the information technologies. For such tasks is characteristic the task of the initial conditions, limitations, structures and parameters of objective functions it is inaccurate which leads to the uncertainty of information and hampers the process of decision making. The problem of decision making under the conditions of uncertainty occupies at present special position in the information technologies. For such tasks is characteristic the task of the initial conditions, limitations, structures and parameters of objective functions it is inaccurate which leads to the uncertainty of information and hampers the process of decision making
Keywords: интервальная неопределенность